SCIENTOMETRIC MAPPING OF TSUNAMI PUBLICATIONS: A CITATION BASED STUDY - Anil, Sagar; B. S., Kademani; R. G., Garg; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2010)
The objective of the study was to perform a scientometric analysis of all Tsunami related publications as per the Scopus TM database during 1997-2008. A total of 4338 publications and 21107 citations to these papers were received. The parameters studied include growth of publication, country-wise distribution of publications, activity index of countries, most-frequently cited publications, authorship pattern, co-authorship index, and distribution of keywords. United States of America, Japan, United Kingdom, India and Australia produced 54.20% of the total output. A spurt in number of publications was observed after the Indonesia’s tsunami occurred on 26 December 2004.